Vague Language in Cigarette Advertising Tagline in Indonesia - Alfin, Jauharoti (Opción, 2019)
In Indonesia, cigarette is viewed from different perspectives. It is a popular and cultured product hated because of the health threat and bad stigma attached to smokers, especially women and children. In its marketing, cigarette producers used vague language as a strategy with the intention of fooling the public on health threats and the bad stigma attached to the product. However, this concept is a sub-study of pragmatics in the theory of communication cooperation containing violations of maxims. Marketers make use of it to make cigarettes acceptable in society. Therefore, the purpo- se of this study was to investigate the function of vague language in adverti- sing tagline of cigarettes in Indonesia. The analysis was based on vague language theory, the principle of cooperation, and conversational implicatu- res with data taken from the cigarette advertisement tagline in the country. The results showed that the use of the concept tends to violate the Maxim of Relevance and Manner with the aim of increasing flexibility, persuasion, provoking consumers, hiding negative values, building identity, and attac- king competitors.